Perbandingan brand equity produk sabun pembersih wajah merek pond’s dengan biore pada mahasiswa fakultas keguruan dan ilmu pendidikan universitas mulawarman samarinda - Ari K. Christian; J. Kuleh; Saida Zainurossalamia ZA (Faculty of Economics and Business Mulawarman University, 2016)
This research aim to know the comparison of brand equity between facial wash product brand ponds with biore. Data analysis technique used is different from the mean test with paired samples. Based on the result of the study, it was found that difference between facial wash brand ponds with biore. Of the four indicators that make up the brand equity, ponds is superior to the biore. Additionaly the Biore expected to increase four indicator shaper brand equity in order to become a top brand of facial wash product.Keyword: Brand Equity, Brand Awareness, Brand Association, Perceived Quality, Brand Loyalty.